Evaluation of Remote Pharmacist-Led Outpatient Service for Geriatric Patients on Rivaroxaban for Nonvalvular Atrial Fibrillation During the COVID-19 Pandemic - Li, Xiaoye; Zuo, Chengchun; Lu, Wenjing; Zou, Ye; Xu, Qing; Li, Xiaoyu; Lv, Qianzhou (Frontiers in Pharmacology, 2020)
Abstract Objective: This study was designed to evaluate the efficacy of remote medication management of rivaroxaban by pharmacists for geriatric patients with nonvalvular atrial fibrillation during the COVID-19 pandemic. Methods: A single, prospective cohort study was conducted among patients with non-valvular atrial fibrillation who received rivaroxaban therapy from July 2019 to December 2019. Patients in the pharmacist-led education and follow-up service (PEFS) group were managed remotely by a pharmacist. In contrast, those in the usual care (UC) group were managed by other providers. Patient data were collected from routine blood tests, coagulation function tests, which also included cardiac function parameters. The number and type of provider encounters, interventions related to rivaroxaban therapy, the occurrence of thromboembolism or bleeding, and the time of the first outpatient visit after discharge were recorded. Results: A total of 600 patients were recruited, and results of 381 patients were analyzed in the end, of which 179 patients were from the PEFS group and 202 were from the UC group. There was no significant difference between the two groups in terms of the occurrence ratio of systemic thrombosis, heart failure (LVEF < 40%), and left atrial dilation, which was defined as enlargement of left atrial diameter (LAD) > 40 mm. The cumulative incidences of bleeding complications, such as gastrointestinal tract and skin ecchymosis, were significantly higher in the UC group (12.4% vs. 6.1%, P=0.038; 4.5% vs. 0.6%, P=0.018). There was no significant difference after pharmacist intervention in terms of thrombosis occurrence ratio between the two groups (P = 0.338, HR: 0.722, 95%CI: 0.372-1.405). Remote instruction by a pharmacist reduced outpatient service frequency within the first 30 days after discharge (23.7% vs. 1.1%, P < 0.001). However, more patients in the PEFS group presented for the first outpatient revisit later than 40 days post-discharge (12.8% vs. 21.3%, P < 0.001). Conclusion: Remote pharmacist-led medication instruction of rivaroxaban could reduce bleeding complications of the gastrointestinal tract and skin ecchymosis and postpone the first outpatient revisit after discharge.